Uma abordagem investigativa para o experimento do plano inclinado / An Investigative Approach to the Experiment of the Inclined Plane - Ueno Guimarães, Michele Hidemi; dos Santos Simões, Bruno (Revista Internacional de Aprendizaje en Ciencia, Matemáticas y Tecnología, 2015)
ABSTRACT This paper aims to discuss the different approaches that can be adopted by students related to the experiment of the inclined plane. In this work we present two proposal: A traditional approach, with a step by step script, where the students assume a passive posture, and the other approach, which seeks to incite an investigative learning, and where the students take an active posture to the experiment and to the script, which could be understood as a process of education through research. Demo (1998) comments that in this process, the students develop more autonomy, criticality and creativity in their own study/work, making their own interpretations, hypothesis formulation, among other things. Zômpero and Laburú (2012) argue that this kind of activity encourages students to become more autonomous, critical and creative. An investigative activity aims to create an investigative environment in science classes so that the teacher can teach (lead / broker) the students in the process (simplified) of scientific work. What is expected is that students would develop autonomy in the analysis of their results and would be more critical before them. Thus, they would have more active attitude towards new knowledge, or in the interpretation of it, handle it or if necessary, reframing the heuristic adopted. RESUMO Este trabalho tem por objetivo discutir as diferentes posturas, que podem ser adotadas por estudantes frente ao expe-rimento do plano inclinado. Apresentamos duas propostas: em uma delas, um roteiro tradicional, com passo a passo, em que o estudante assume uma postura passiva frente ao roteiro; e outra, que busca incitar a uma aprendizagem investigativa, mediante a qual o aluno assume uma postura ativa frente ao experimento e ao roteiro, o que poderia ser entendido como um processo de educar pela pesquisa. Demo (1998) comenta que, nesse processo, o estudante desenvolve autonomia, criticidade sobre seu estudo/trabalho, faz interpretações próprias, formula hipóteses, entre outros fatores. Zômpero e Laburú (2012) argumentam que esse tipo de atividade favorece aos estudantes a se tornarem mais autônomos, críticos e criativos. Uma atividade investigativa tem como objetivo criar um ambiente investigativo nas aulas de Ciências, de maneira que o professor possa ensinar (condu-zir/mediar) os alunos no processo (simplificado) do trabalho científico. O que se espera é que os educandos desenvolvam auto-nomia na análise dos resultados obtidos e que sejam críticos acerca deles, tendo assim uma atitude ativa frente ao novo conhe-cimento, seja para interpretá-lo, manipulá-lo ou se necessário, ressignificar a heurística adotada. Contato principal: micheleueno@usp.br